Saphenous vein graft aneurysm after coronary artery bypass graft surgery: A case report - Reyhanoğlu, Hasan; Özcan, Kaan; Edem, Efe (Journal of Surgery and Medicine, 2020)
Aneurysm of the saphenous vein, which is the most used graft in coronary bypass surgery, is a rare complication. While saphenous vein dilatation forming in the early or late stages after bypass surgery can be symptomatic, it can also be diagnosed incidentally. Aneurysms forming in the late stages are atherosclerotic while those forming in the initial stages are mostly connected to venous damage. In the present case, a saphenous aneurysm with atherosclerotic causes was detected in a patient 20 years after coronary bypass surgery. The patient was admitted with chest pain, syncope, and dizziness complaints. Examination revealed a saphenous vein aneurysm measuring 28x30 mm. The patient underwent surgery, and the aneurysm was resected.